Brachyuran community in Ubatuba Bay, northern coast of São Paulo State, Brazil - Mantelatto, FLM; Fransozo, A. (Natl Shellfisheries Assoc, 2000)
A bruchyuran crab assemblage from eight transacts at a non-consolidated sublittoral site in Ubatuba Bay was studied on a monthly basis from September 1995 to August 1996. Data about number of individuals of 50 species found and other information such as distribution of the dominant crabs are reported. The family Majidae was represented by 13 species, followed by Xanthidae (13), Portunidae (10), Leucosiidae (5), Calaphidae (2), Dromiidae (2), Parthenopidae (2), Goneplacidae (1), Pinnotharidne (1), and Ocvpodidae (1). The brachyuran taxocoenosis was dominated by Callinectes ornatus (60.4%), Callinectes danae (18.8%), and Hepatus pudibundus (7.7%). representing together 86.9% of the total number of collected brachyurans. The Shannon-Weaver diversity index ranged from 1.10 to 2.06 between transects, and from 1.33 to 2.22 between months, depending more on equitability than on richness.
Keywords: biodiversity; Brachyura; crabs; Crustacea; Ubatuba; Brazil